2020
DOI: 10.3390/cryst10040332
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Mechanical Properties of Al/SiC by Utilizing Different Ball Milling Speeds

Abstract: Advanced materials with high strength are in great demand for structural applications, such as in aerospace. It has been proved that fabrication strategy plays a vital role in producing composites to satisfy these needs. This study explores new strategies for flake powder metallurgy, with the aim of designing an effective strategy to achieve the highest possible mechanical strength for a metal matrix nanocomposite without changing the reinforcement fraction. Different strategies were used to regulate the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…for 8 h, provided the machine cools for 10 min at each 1 h interval. [ 23 ] After the ball milling of pure Cu powder, it was sieved and the fine particles were separated. Then, the sieved Cu powder (50−37 μm) was mixed with initial SiC powder in the metal−ceramic wt% ratios of 90/10 and 80/20.…”
Section: Methodsmentioning
confidence: 99%
“…for 8 h, provided the machine cools for 10 min at each 1 h interval. [ 23 ] After the ball milling of pure Cu powder, it was sieved and the fine particles were separated. Then, the sieved Cu powder (50−37 μm) was mixed with initial SiC powder in the metal−ceramic wt% ratios of 90/10 and 80/20.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, samples were hot extruded at extrusion ration of 16:1 under the flow of argon gas [73]. Microstructure and properties of metal matrix nanocomposites were influenced by process parameters in powder metallurgy method [74]. Salur et al [75] reported influence of milling time on microstructure of Y 2 O 3 nanoparticle reinforced aluminium matrix composite.…”
Section: Fabrication Of Ceramic Nanoparticle Reinforced Aluminum Matr...mentioning
confidence: 99%
“…As compared with base alloy materials, compressive strength and micro hardness of the hybrid nanocomposite has been improved 26.5 and 40%, respectively [102]. Better load carrying properties of the nanocomposite materials was due to the decrease in grain structure, uniform dispersion and distribution of nanomaterials, and formation of dislocation because of the thermal mismatch between aluminium and ceramic nanoparticles [74]. Mechanical and wear properties of alumina and graphene oxide incorporated aluminium matrix hybrid nanocomposites has been described by Mohammed et al [103].…”
Section: Properties Of Ceramic Nanoparticle Reinforced Aluminum Matri...mentioning
confidence: 99%
“…A high-frequency induction-heated sintering (HFIHS) process is one of the most effective consolidation techniques in which simultaneous pressure and temperature are applied to the powder mixture sample in a vacuumed atmosphere within a very short time to produce a high-density and homogeneous composite [29,30]. This advanced sintering process is beneficial because its densification ability is very good, which produces high-density samples with convergent real and theoretical densities, i.e., relative density is very close to 100% [31].…”
Section: Introductionmentioning
confidence: 99%